Psychological First Aid: Meningkatkan Kompetensi Guru saat Menghadapi Situasi Krisis pada Siswa: Psychological First Aid: Enhancing Teachers’ Competence in Responding to Students’ Crisis Situations - Aryuni, Muthia; Jane Mariem Monepa; I Putu Fery Immanuel White; Miranti; Meilisa Silviana Patodo (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2025)
Teachers play a vital role in providing initial psychological support to students experiencing crisis situations; however, most educators still lack adequate Psychological First Aid (PFA) skills. This study aims to enhance and examine the effectiveness of PFA training in improving teachers’ competencies in handling students’ psychological crises. A quantitative approach with a quasi–experimental one-group pretest–posttest design was utilized. The study involved all 31 teachers at SMP Negeri Model Terpadu Madani, Palu, selected using a total sampling technique. Research instruments consisted of a PFA knowledge test and observation sheets. Data were analyzed using descriptive statistics and N-Gain Score calculations. The findings revealed an increase in the average score from 43.87 (pretest) to 89.35 (posttest), with an N-Gain value of 81.5%, categorized as effective. These results indicate that PFA training successfully improved participants’ knowledge, practical skills, and readiness to provide initial psychological support to students experiencing psychological distress. This program is recommended for sustained implementation and replication in other schools, particularly in disaster-prone regions.